The Effect of Environmental Social Governance on the Company's Financial Performance with Company Size as a Moderating Variable - Qofi’ah, Rohmawati; Lismawati, Lismawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine how the impact of ESG on the financial performance of manufacturing companies in Indonesia. The population of this study is 35 companies in a 4-year period, so the sample includes 140 companies. This study applies a quantitative approach with data analysis through panel data regression and Moderated Regression Analysis (MRA) is implemented to determine whether the company size variable can strengthen or weaken the correlation of ESG's influence on financial performance with Eviews 12. The test results with panel data regression implementing the Fixed Effect Model (FEM) indicate the t-statistic value for the ESG variable is -2.153039 which indicates that ESG has a negative impact on financial performance and company size as moderation is able to weaken the correlation of ESG to the financial performance of manufacturing companies in Indonesia listed on the IDX during the 2020-2023 period.